Canagliflozin and renal outcomes in type 2 diabetes: results from the CANVAS Program randomised clinical trials. Issue 9 (September 2018) - Perkovic, Vlado; de Zeeuw, Dick; Mahaffey, Kenneth W; Fulcher, Greg; Erondu, Ngozi; Shaw, Wayne; Barrett, Terrance D; Weidner-Wells, Michele; Deng, Hsiaowei; Matthews, David R; Neal, Bruce
Summary: Background: In the Canagliflozin Cardiovascular Assessment Study (CANVAS) Program, canagliflozin reduced the rates of major adverse cardiovascular events and the results suggested a renal benefit in patients with type 2 diabetes who were at high risk for cardiovascular events, compared with those treated with placebo. Here we report the results of a prespecified exploratory analysis of the long-term effects of canagliflozin on a range of sustained and adjudicated renal outcomes. Methods: The CANVAS Program consists of two double-blind, randomised trials that assessed canagliflozin versus placebo in participants with type 2 diabetes who were at high risk of cardiovascular events, done at 667 centres in 30 countries. People with type 2 diabetes and an HbA1c of 7·0–10·5% (53–91 mmol/mol) who were aged at least 30 years and had a history of symptomatic atherosclerotic vascular disease, or who were aged at least 50 years and had at least two cardiovascular risk factors were eligible to participate. Participants in CANVAS were randomly assigned (1:1:1) to receive 300 mg canagliflozin, 100 mg canagliflozin, or matching placebo once daily. Participants in CANVAS-R were randomly assigned (1:1) to receive canagliflozin or matching placebo, at an initial dose of 100 mg daily, with optional uptitration to 300 mg from week 13 or matching placebo. Participants and all study staff were masked to treatment allocations until study completion. Prespecified outcomes reported here include a composite of sustained and adjudicated doubling in serum creatinine, end-stage kidney disease, or death from renal causes; the individual components of this composite outcome; annual reductions in estimated glomerular filtration rate (eGFR); and changes in urinary albumin-to-creatinine ratio (UACR). The trials are registered withClinicalTrials.gov, numbersNCT01032629 (CANVAS) andNCT01989754 (CANVAS-R). Findings: Between Nov 17, 2009, and March 7, 2011 (CANVAS), and Jan 17, 2014, and May 29, 2015 (CANVAS-R), 15 494 people were screened, of whom 10 142 participants (with a baseline mean eGFR 76·5 mL/min per 1·73 m 2, median UACR 12·3 mg/g, and 80% of whom were receiving renin–angiotensin system blockade) were randomly allocated to receive either canagliflozin or placebo. The composite outcome of sustained doubling of serum creatinine, end-stage kidney disease, and death from renal causes occurred less frequently in the canagliflozin group compared with the placebo group (1·5 per 1000 patient-years in the canagliflozin group vs 2·8 per 1000 patient-years in the placebo group; hazard ratio 0·53, 95% CI 0·33–0·84), with consistent findings across prespecified patient subgroups. Annual eGFR decline was slower (slope difference between groups 1·2 mL/min per 1·73 m 2 per year, 95% CI 1·0–1·4) and mean UACR was 18% lower (95% CI 16–20) in participants treated with canagliflozin than in those treated with placebo. Total serious renal-related adverse events were similar between the canagliflozin and placebo groups (2·5 vs 3·3 per 1000 patient-years; HR 0·76, 95% CI 0·49–1·19). Interpretation: In a prespecified exploratory analysis, canagliflozin treatment was associated with a reduced risk of sustained loss of kidney function, attenuated eGFR decline, and a reduction in albuminuria, which supports a possible renoprotective effect of this drug in people with type 2 diabetes. Funding: Janssen Research & Development.